A new Anyphaena species from China (Araneae: Anyphaenidae) - Zhang, Feng; Zhu, Ming-Sheng; Song, Da-Xiang (Zootaxa, 2005)
Anyphaena wuyi sp. nov. is described by means of two males and two females from Wuyi Mountain of Fujian Province, China. It is also recorded from Daozhen County of Guizhou Province, China. According to examined characters it belongs to the pacifica-group. The species Anyphaena liuyangensis Xu, Yin & Yan, 2002 is considered a junior synonym of Cheiracanthium fibrosum Zhang, Hu & Zhu, 1994 (new synonymy).